Study of Morphology of the Spotted Stream Frog Pulchrana sundabarat (Chan, Abraham, Grismer, and Brown, 2020) in West Sumatera - Fajri Adhiyat Rifyant; Fitra Arya Dwi Nugraha (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Indonesia is a country that has the highest mega-biodiversity in the world. The number of species reported throughout the year increased for both amphibians and reptiles. In the territory of Indonesia, many types of anura are widely distributed and hindered by physical obstacles such as hills, mountains or the sea. One of the most widely distributed species is Pulchrana sundabarat which is found in southern Thailand, Peninsular Malaysia and Sumatra. However, previous researchers only analyzed specimens that only came from specimens that had been studied in Peninsular Malaysia. This study aims to determine the variation of morphological characters of Pulchrana Sundabarat in Sumatra, especially West Sumatra. This study used the Visual Encounter Survey (VES) method for sampling and the data obtained were analyzed descriptively and presented in tabular form. The results of this study found 11 individuals of Pulchrana Sundabarat from 4 different areas, including 9 males and 2 females. The distinguishing characteristics include body size, head shape and size, body pattern (dorsolateral line shape and color), color and distribution of spots on the dorsal, lateral and ventral sides.